A Retrospective qualitative analysis of the implementation of rule X of the republic act 9003 on solid waste management in Las Pinas City, Philippines - La Puebla, Ferdinand Leal (UP Los Baños Journal, 2016)
This study was conducted to analyze compliance with Rule X, Section 1 of the Republic Act 9003 otherwise known as the Ecological Solid Waste Management (SWM) Act of 2000 of Las Pinas City, a "cleanest cities" awardee from 1997-1999. Baseline study findings in 2005 were revisited and compared to findings in 2016 using key informant interviews with the Environmental and Sanitation Office ( ESO) and with the City Health Office (CHO) and its technical division in-charge on health promotion, observations during the collections, policy analysis, assisted survey questionnaire administration, and quick telephone interviews. The triangulation method was then applied. Findings reveal that there has been no added value after 11 years (2005-2016) of the city's implementation of the SWM Act: Personal protective equipment (PPE) are not fully provided, no clear coordination or joint partnership between ESO and CHO as to the conduct health education and promotion environment and protection of garbage operators from hazards and risks, health problems are becoming common, consultations are based on walk-in basis and not regular, and last, CHO has not been a member of the Local City Solid Waste Management Board (LCSWMB) since 2005. In conclusion, Las Pinas City is not compliant with Rule X, Section 1 of the Implementing Rules and Regulations of Republic Act of 9003 and other SWM-related policies based on 2005 and March 2016. Compliance with other matters such as those concerning spillage and cleaning of trucks was partial. Rule x of RA 9003 seems to be a sufficient policy to protect the health and safety of garbage operators and the public in general, however, it is very evident that strict implementation of the law is needed.